Photosensitized generation of singlet oxygen from vinyl linked benzo-crown-ether-bipyridyl ruthenium(II) complexes - Abdel-Shafi, A; Beer, P; Mortimer, R; Wilkinson, F (2000)
Photophysical properties of 10 substituted methoxybenzene or vinyl linked benzo-crown-ether-2,2′-bipyridyl ruthenium(II) complexes are reported. The lifetimes of the excited triplet metal to ligand charge transfer states, 3MLCT, of the complex ions are in the range 0.85 ± 0.12 μs with two exceptions where the lifetime drops to about half this value. The rate constants, kq, for quenching in acetonitrile of the 3MLCT states of these ruthenium complex ions by molecular oxygen, O2(3∑g-), and the variations in the efficiency, fΔT, with which excited singlet oxygen, O2*(1Δg), is thereby produced are reported. The quenching rate constants are in the range 2.2-4.2 × 109 dm3 mol-1 s-1, and efficiencies of singlet oxygen production are in the range 0.21-0.74. Those complexes with the highest values of kq tend to be those with lowest fΔT values; that is, kq and fΔT show a reasonable inverse correlation. The product kqfΔT gives the rate constant for oxygen quenching with energy transfer to oxygen, kq1, and kq - kq1 gives the rate constant, kq3, for oxygen quenching by any path which does not lead to energy transfer. The values of kq1, kq3, and kq are compared with those in the literature which are mainly available for organic sensitizers of singlet oxygen. The similarities and differences between these two classes of compounds are discussed taking into account the fact that ruthenium complex ions are likely to show enhanced intersystem crossing, due to the heavy atom effect and the likely dependence of kq1 and kq3, and thereby the efficiencies of singlet oxygen production, on the energies of the excited 3MLCT states and on steric factors.